Prognostic impact of neutrophil‐to‐lymphocyte ratio in cirrhosis: A propensity score matching analysis with a prespecified cut‐point. (29th August 2019) - Deng, You; Fan, Xiaofei; Ran, Ying; Xu, Xin; Lin, Lin; Cui, Binxin; Hou, Lijun; Zhao, Tianming; Wang, Ya; Su, Zhengyan; Jiang, Xihui; Zhao, Wei; et al.
Abstract: Background & Aims: An elevated neutrophil‐to‐lymphocyte ratio (NLR) has received attention as a prognostic surrogate across chronic liver diseases. However, an exact threshold has not been fully elucidated. Methods: A total number of 589 patients with cirrhosis (LC) were included. The value of NLR was calculated and its optimal cut‐off was initially determined by X‐tile program. Independent predictors of 90‐day mortality were identified with Cox regression model. The Kaplan‐Meier method was used to generate survival curves. To reduce influences of selection bias and possible confounders, a 1:2 propensity score matching (PSM) was performed. Results: The X‐tile indicated that the difference in survival was most significant for NLR more than 8.9. Serum NLR > 8.9 was an independent indicator in the entire cohort and PSM subset (HR 4.268, 95% CI 2.211‐8.238, P < .001; HR 4.209, 95% CI 1.448‐12.238, P = .008 respectively). Subgroup analysis showed that NLR > 8.9 was an independent risk factor of 90‐day mortality regardless of age, gender, CTP or MELD score. Conclusions: The value of NLR more than 8.9 is a feasible cut‐off across clinical settings among applicable population. The adding of NLR to other conventional predictive systems has the potential to provide incremental value without extra economic cost.